Groove-structured meta-surface for patterned sub-diffraction sound focusing - Chen, Jian (2019)
Confining acoustic fields in subwavelength volumes is of fundamental interest in wave-energy harvesting and high-resolution imaging. Phononic crystals have been shown to be capable of superfocusing but are highly limited by their very large dimensions. Acoustic metasurfaces can yield similar functionality with unit cells significantly smaller than the wavelength. However, they are studied mostly under effective medium theory and cannot manipulate evanescent waves directly to control near-field focusing. Here, we use a microscopic approach to study acoustic metasurfaces for subdiffraction focusing of reflected waves, which consist of an array of deep-subwavelength sized and spaced grooves. We further show that the focusing pattern can be tailored by the designer. To validate the effectiveness of our scheme, two representative metasurfaces are designed theoretically, proved numerically, and confirmed experimentally for subdiffraction sound focusing with different patterns. We hope that our approach can work as a general guideline to shape near-field signals in the broad field of acoustics.